Cdc42 regulates Cdc42EP3 function in cancer-associated fibroblasts. (2nd January 2017) - Farrugia, Aaron J.; Calvo, Fernando
ABSTRACT: Rho family GTPases such as Cdc42 are key regulators of essential cellular processes through their effects on cytoskeletal dynamics, signaling and gene expression. Rho GTPases modulate these functions by engaging a wide variety of downstream effectors. Among these effectors is the largely understudied Cdc42EP/BORG family of Cdc42 effectors. BORG proteins have been linked to actin and septin regulation, but their role in development and disease is only starting to emerge. Recently, Cdc42EP3/BORG2 was shown to coordinate actin and septin cytoskeleton rearrangements in cancer-associated fibroblasts (CAFs). Interestingly, Cdc42EP3 expression potentiated cellular responses to mechanical stimulation leading to signaling and transcriptional adaptations required for the emergence of a fully activated CAF phenotype. These findings uncover a novel role for the BORG/septin network in cancer. Here, we demonstrate that Cdc42EP3 function in CAFs relies on tight regulation by Cdc42.